GAMBARAN STATUS GIZI (IMT, LILA DAN LINGKAR PINGGANG) WANITA PRA NIKAH DIWILAYAH KERJA PUSKESMAS ALAK - hana nursalina; Asmulyati S Saleh; Agustina Setia (Kupang Journal of Food and Nutrition Research, 2026)
The nutritional status of women before marriage significantly impacts their physical readiness and reproductive health. An unbalanced diet—whether due to deficiency or excess—can affect fertility and fetal health. Women with undernutrition may experience menstrual irregularities, difficulty conceiving, or give birth to low-birth-weight babies. Meanwhile, overnutrition can lead to obesity and pregnancy complications. Therefore, maintaining a balanced diet before marriage is crucial for supporting pregnancy and the health of both the mother and the baby. According to the results of the 2023 Indonesia Health Survey, the prevalence of BMI-based nutritional status in NTT Province was 14.5% wasting, 56.3% normal, 12.1% overweight, and 17.1% obese, while the prevalence of KEK was 28.0% among pregnant women and 35.7% among non-pregnant women. This study aims to determine the nutritional status (BMI, mid-upper arm circumference, and waist circumference) of premarital women. The study design used was a quantitative descriptive study with a cross-sectional approach. The study results show that the majority of respondents had a BMI-based nutritional status in the normal category (65.3%), while 27.8% were overweight and 6.9% were underweight. Based on LILA measurements, the majority of respondents fell into the normal category (88.9%), while 13.9% were at risk of Chronic Energy Deficiency (CED). Meanwhile, waist circumference measurements indicated that 37.5% of respondents were in the obese category. The nutritional status of premarital women in the Alak Community Health Center’s service area is mostly normal. However, some still suffer from obesity; therefore, regular nutrition education and monitoring are necessary.